Ответ:
1. [tex]-a^{5} +3a^{2} b+31a^{3} b+5b^{2}[/tex]
2. [tex]-3m^{5} -26m^{3} n-3m^{2} n-6n^{2}[/tex]
Объяснение:
1. [tex](3a^{2} +5b)(2a^{3} +b)-7a^{3} (a^{2} -3b) = 6a^{5} +3a^{2} b+10a^{3} b+5b^{2} -7a^{5}+21a^{3} b = -a^{5} +3a^{2} b+31a^{3} b+5b^{2}[/tex]
2. [tex](m^{3} -3n)(m^{2} +2n)-4m^{3} (m^{2} +7n)=m^{5} +2m^{3} n-3m^{2} n-6n^{2} -4m^{5} -28m^{3} n = -3m^{5} -26m^{3} n-3m^{2} n-6n^{2}[/tex]
думаю правильно:)))))
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Ответ:
1. [tex]-a^{5} +3a^{2} b+31a^{3} b+5b^{2}[/tex]
2. [tex]-3m^{5} -26m^{3} n-3m^{2} n-6n^{2}[/tex]
Объяснение:
1. [tex](3a^{2} +5b)(2a^{3} +b)-7a^{3} (a^{2} -3b) = 6a^{5} +3a^{2} b+10a^{3} b+5b^{2} -7a^{5}+21a^{3} b = -a^{5} +3a^{2} b+31a^{3} b+5b^{2}[/tex]
2. [tex](m^{3} -3n)(m^{2} +2n)-4m^{3} (m^{2} +7n)=m^{5} +2m^{3} n-3m^{2} n-6n^{2} -4m^{5} -28m^{3} n = -3m^{5} -26m^{3} n-3m^{2} n-6n^{2}[/tex]
думаю правильно:)))))